2019
DOI: 10.1093/biolinnean/bly218
|View full text |Cite
|
Sign up to set email alerts
|

Back to the wild: does feralization affect the mandible of non-commensal house mice (Mus musculus domesticus)?

Abstract: If domestication has been well studied lately with the recognition of a so-called 'domestication syndrome', the opposite process, feralization, has deserved much less interest. The commensal Western European house mouse (Mus musculus domesticus) lives in close contact to humans, a situation setting it between wild and domesticated animals. However, the house mouse also occurs in non-anthropogenic environments, forming feral populations and hence providing the opportunity to document how feralization may impact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…In many mammals, the size and shape of skeletal and dental elements can be both influenced by intrinsic and extrinsic factors (Scott 1987 ; Kappelman 1988 ; DeGusta and Vrba 2005 ; Eronen et al 2006 ; Klein et al 2010 ; Polly 2010 ; Meachen et al 2016 ; Ledevin et al 2016 ; Renaud et al 2018 ; Pelletier 2018 , 2019 ; Souquet et al 2019 ). It has been shown that some of these parameters, such as geographic position, topography or marked variations in climate and the environment, could also notably influence the body size and/or morphology of reindeer (Thomas and Everson 1981 ; Collins and Smith 1991 ; Weinstock 1997 , 2002 ; Weladji and Holand 2003 , 2006 ; Weladji et al 2003 ; Reimers et al 2005 ; Mårell et al 2006 ; Magniez 2010 ).…”
Section: Methodsmentioning
confidence: 99%
“…In many mammals, the size and shape of skeletal and dental elements can be both influenced by intrinsic and extrinsic factors (Scott 1987 ; Kappelman 1988 ; DeGusta and Vrba 2005 ; Eronen et al 2006 ; Klein et al 2010 ; Polly 2010 ; Meachen et al 2016 ; Ledevin et al 2016 ; Renaud et al 2018 ; Pelletier 2018 , 2019 ; Souquet et al 2019 ). It has been shown that some of these parameters, such as geographic position, topography or marked variations in climate and the environment, could also notably influence the body size and/or morphology of reindeer (Thomas and Everson 1981 ; Collins and Smith 1991 ; Weinstock 1997 , 2002 ; Weladji and Holand 2003 , 2006 ; Weladji et al 2003 ; Reimers et al 2005 ; Mårell et al 2006 ; Magniez 2010 ).…”
Section: Methodsmentioning
confidence: 99%
“…Although mechanical advantage makes mechanical sense and has previously been used as a proxy for function (e.g. Thorington and Darrow, 1996;Velhagen and Roth, 1997;Swiderski and Zelditch, 2010;Blanco et al, 2013;Casanovas-Vilar and van Dam, 2013;Gomes Rodrigues et al, 2016;Fabre et al, 2017;Renaud et al, 2015Renaud et al, , 2018aParmenter et al, 2019;Souquet et al, 2019), its relationship with bite force has never been formally tested. The mechanical expectation is that individuals with larger values for mechanical advantage will show larger bite forces.…”
Section: Introductionmentioning
confidence: 99%
“…However, given that most were caught in the vicinity of agricultural storage places, it would seem likely that their food is biased towards usage of grains. Analysis of feral mice coming from non-commensal regions has shown that their mandible shapes change towards a more carnivorous type, possibly due to plasticity effects [21][22][23][24], implying that the commensal life-style is characterized by more starch-rich diets. Given this general observation and the fact that the mice studied here have a common commensal origin, one would have expected similar ).…”
Section: The Amylase Cluster Genomic Regionmentioning
confidence: 99%